Bacterial Community Structure and Environmental Driving Factors in the Surface Sediments of Six Mangrove Sites from Guangxi, China - Ying Liu; Songze Chen; Jinyu Liang; Jingjing Song; Yue Sun; Riquan Liao; Mingzhong Liang; Hongming Cao; Xiuhao Chen; Yuxia Wu; Liting Bei; Yuting Pan; et al. (Microorganisms)
Mangroves, as blue carbon reservoirs, provide a unique habitat for supporting a variety of microorganisms. Among these, bacteria play crucial roles in the biogeochemical processes of mangrove sediments. However, little is known about their community composition, spatial distribution patterns, and environmental driving factors, particularly across the large geographical scales of mangrove wetlands. In this study, the composition and spatial distribution of the bacterial community structure and its response to fifteen physicochemical parameters (including temperature, pH, salinity, moisture, clay, silt, sand, organic carbon (OC), total nitrogen (TN), total phosphorus (TP), inorganic phosphorus (IP), organic phosphorus (OP), δ13C, δ15N, and carbon/nitrogen ratio (C/N ratio)) were characterized in 32 sampling locations of six different mangrove habitats from Guangxi, China, applying 16S rRNA gene high-throughput sequencing technology and correlation analysis. Our results indicated that the spatial distribution patterns in bacterial communities were significantly different among the six different mangrove sites, as evidenced by NMDS (non-metric multidimensional scaling), ANOSIM (analysis of similarity), and LDA (linear discriminant analysis) analysis. Composition analysis of bacterial communities showed that overall, Chloroflexi (8.3–31.6%), Proteobacteria (13.6–30.1%), Bacteroidota (5.0–24.6%), and Desulfobacterota (3.8–24.0%) were the most abundant bacterial phyla in the mangrove surface sediments. Redundancy analysis (RDA) further highlighted that salinity, δ13C, temperature, δ15N, and silt were the most critical environmental variables influencing the composition of bacterial communities across the whole mangrove samples. Notably, Chloroflexi, one of the most abundant bacterial phyla in the mangrove wetlands, displayed a significantly positive correlation with OC and a negative correlation with δ13C, suggesting its essential role in the degradation of terrestrial-derived organic carbon. These findings support the current understanding of the roles of the bacterial communities and their interactions with environmental factors in diverse mangrove ecosystems.